FAKTOR-FAKTOR YANG MEMPENGARUHI RETURN SAHAM PADA PERUSAHAAN MANUFAKTUR DI INDONESIA - Willi Sunandi; Augustpaosa Nariman (Jurnal Paradigma Akuntansi, 2022)
The purpose of this research was to examine the influence profitability, leverage, and firm size in manufacture companies listed in the Indonesian Stock Exchange in 2017-2019. The sample was determined by using purposive sampling method by taking 70companies each year with a total of 210 samples. The data was processed with Eviews 11 by using multiple regression technique. The result showed that firm size had positive effect on stock return, while profitability and leverage had no effect on stock return. The implication of this study was the need to increase firm size to increase stock return of companies because of incresing investment from investor.